2022
DOI: 10.1021/acs.jpclett.2c02618
|View full text |Cite
|
Sign up to set email alerts
|

Competition between In-Plane vs Above-Plane Configurations of Water with Aromatic Molecules: Non-Covalent Interactions in 1,4-Naphthoquinone-(H2O)1–3Complexes

Abstract: Non-covalent interactions between aromatic molecules and water are fundamental in many chemical and biological processes, and their accurate description is essential to understand molecular relative configurations. Here we present the rotational spectroscopy study of the water complexes of the polycyclic aromatic hydrocarbon 1,4-naphthoquinone (1,4-NQ). In 1,4-NQ-(H2O)1,2, water molecules bind through O–H···O and C–H···O hydrogen bonds and are located on the plane of 1,4-NQ. For 1,4-NQ-(H2O)3, in-plane and abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…[9][10][11] When the aromatics contain heteroatoms or functional groups, water switches to the edgeways bind them with an in-plane configuration. [11][12][13][14] As the number of water molecules grows, complicated competition between in-plane and above-plane configurations of water molecules might emerge. 14 Besides, charge distributions and structural changes can be observed to be prominent dependent on stepwise complexation with H 2 O.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11] When the aromatics contain heteroatoms or functional groups, water switches to the edgeways bind them with an in-plane configuration. [11][12][13][14] As the number of water molecules grows, complicated competition between in-plane and above-plane configurations of water molecules might emerge. 14 Besides, charge distributions and structural changes can be observed to be prominent dependent on stepwise complexation with H 2 O.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] As the number of water molecules grows, complicated competition between in-plane and above-plane configurations of water molecules might emerge. 14 Besides, charge distributions and structural changes can be observed to be prominent dependent on stepwise complexation with H 2 O. 15,16 Indeed, it has been shown that the bond lengths r(Na-Cl) increase with the growth of the number of water molecules.…”
Section: Introductionmentioning
confidence: 99%
“…19 When water is the solvent, it seems that the HB is preferentially formed with the electronegative heteroatom. This behaviour has been observed on a heterocyclic oxy-PAH (dibenzofuran), 20 a partially aromatic oxy-PAH (naphthoquinone), 21 a cyano-PAH 22 and a heterocyclic nitro-PAH. 23 Nonetheless, an interesting slightly different case deserves investigation: the hydration of a homocylic oxy-PAH which contains a functional group attached to fully aromatic rings.…”
Section: Introductionmentioning
confidence: 78%
“…Finally, the experimental results call for caution regarding the calculation methods. 21 In the case of β-naphthaldehyde where two monohydrates are predicted within less than 2 kJ mol −1 , namely trans -β-I and trans -β-II, experiments clearly point toward the latter being the most stable structure. This is in agreement with the prediction at the MP2/aug-cc-pVTZ level.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation